Re-evaluating Emotional Awareness and Anthropomorphism in AI Customer Service: Role of Social Presence, and Psychological Distance on Purchase Intention - Jiang, Yue; Kiaw, Jasmine Phan Ah; Mun, Yong Shee (International Review of Management and Marketing, 2026)
The adoption of Artificial Intelligence-driven customer service systems is transforming consumer interactions. Nevertheless, there remains a limited understanding of how specific characteristics of AI in particular emotional awareness and anthropomorphism influence consumer decision-making. This study aims to investigate how these AI traits influence consumers’ perceptions of social presence and psychological distance, and how these perceptions shape trust and intention to use AI services. The findings reveal that emotional awareness significantly enhances social presence and reduces psychological distance. However, while anthropomorphic cues effectively build trust, they exhibit diminishing returns when excessive human-like traits trigger discomfort due to subtle but noticeable imperfections known as ‘uncanny valley’ effect. Moreover, contrary to expectations, social presence does not directly impact the willingness to use AI services, which suggests that functional efficiency may outweigh emotional engagement in service contexts. This research contributes to the literature on human-AI interaction by integrating psychological distance theory with anthropomorphism frameworks.